Evidence of a Large Debris Avalanche Event (22.0 Ma) from the Comondú Group on the Baja California Sur Peninsula, Mexico - Alquiza, María J.P.; Aviles, Raúl M.; Kshirsagar, Pooja V.; Zanor, Gabriela A. (Global Journal of Earth Science and Engineering, 2024)
The morphological, sedimentological, and microtextural characteristics of Miocene debris avalanche deposits which extend from the Punta Coyote to the vicinity of the city of La Paz, were studied along the eastern of the Baja California Peninsula. The debris avalanche deposits studied include a mixture of angular mega blocks whose composition comes from the deposits that make up the Comondú Group: pre-Comondú (red sandstones and conglomerates with intercalated ignimbrites), the Upper Unit (brownish sandstones, shales, and conglomerate), and breccia, with a predominance of jigsaw cracks, injection structures, and fault structures. These deposits were studied and analyzed considering the stratigraphic relationships between the rock formations present in the mega-blocks. Six stratigraphic sections were measured to describe the composition and morphology of the clastic components present in the mega-blocks of the debris avalanche. Two different units (m1 and m2), were identified in the debris avalanche deposits. Unit m1 is the oldest, with a thickness of 100m, and consists of a chaotic set of mega-blocks up to 100 m in diameter derived from the pre-Comondú Group, and Upper Unit. The deposits are highly heterolithic, with angular and highly fractured clasts at different scales. While the unit m2 consists principally of 20-100 m thick volcaniclastic layers dominated by poorly sorted, breccias and minor epiclastic deposits. According to stratigraphic relationships, the collapse occurred at 22.0 Ma. The debris deposit covers an area of 150 km2 and has an estimated volume of 1.3 km3. The characteristic suggests a transport mechanism with a disintegration of the mega-blocks and a contact/collision interaction. Where mega-blocks moved within a dense flow in a buffered manner, remaining consistent over long distances. The observed structures and textures suggest that the mega-blocks were mainly produced by the alteration and ingestion of older substrates by the avalanche of moving debris. The avalanche flowed over pre-existing topography excavated in the Comondú Group sequence, and flow indicators reveal a west-southwest direction, exhibiting a typical mountainous avalanche topography. The study of ancient debris avalanche events not only provides a deeper understanding of these natural phenomena but also contributes to the development of tools to predict, mitigate, and manage risk areas.